"Always trying to walk a bit of a tightrope": The role of social care staff in supporting adults with intellectual and developmental disabilities to develop and maintain loving relationships. (13th February 2020) - Bates, Claire; McCarthy, Michelle; Milne Skillman, Karen; Elson, Nicola; Forrester‐Jones, Rachel; Hunt, Siobhan
Accessible Summary: Support staff play an important role in helping people with learning disabilities to meet a partner and have a relationship. Not getting good support can make it difficult for people to have a relationship. Many support staff want to help people to have a relationship, but are worried about people being abused. This is especially true for those who do not have a lot of staff support. Support staff do not always get good support themselves to help people with learning disabilities to have relationships, such as training and a policy to follow. This makes it hard for them to know what they are allowed to help with. Abstract: Background: People with intellectual and developmental disabilities face challenges in developing and maintaining intimate relationships, frequently requiring support from staff. Method: Focus groups were conducted with 26 social care staff members to explore the support they provided to people with intellectual and developmental disabilities to find a potential partner and/or develop an existing relationship. Results: Staff reported that many people with intellectual and developmental disabilities wanted to be in a relationship and that they did what they could to facilitate this, sometimes providing substantial support. Some staff had to address complex issues relating to sexuality, often with no training and with a lack of clear organisational policies. Conclusion: The need for external inspection and regulatory bodies to prioritise relationship support is emphasised.